Growth and Production Performances of Crossbred Climbing Perch Koi, Anabas testudineus in Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2013)
The study was performed for evaluating the growth and production performances of crossbred climbing perch (Anabas testudineus) during August to October 2009. The crossbred groups of fish were produced by crossing between native climbing perch and Thai climbing perch (A. testudineus). Growth and production performances was compared at grow out condition between crossbred groups in the two reciprocal crosses of treatments viz. T1: Native climbing perch (?) × Thai climbing perch (?) and T2: Thai climbing perch (?)×Native climbing perch (?. At the same time, they were compared also with their respective control F1 pure line groups i.e. T3: Native climbing perch (?) × Native climbing perch (?) and T4: Thai climbing perch (?) × Thai climbing perch (?). It was evident from the results that among the treatments in grow out system, the highest mean harvesting weight was 69.25±9.01 g found in T4 (Thai climbing perch), which was significantly different (P